The folding, stability and function of lactose permease differ in their dependence on bilayer lipid composition. Issue 1 (December 2017) - Findlay, Heather; Booth, Paula
Abstract Lipids play key roles in Biology. Mechanical properties of the lipid bilayer influence their neighbouring membrane proteins, however it is unknown whether different membrane protein properties have the same dependence on membrane mechanics, or whether mechanics are tuned to specific protein processes of the protein. We study the influence of lipid lateral pressure and electrostatic effects on thein vitro reconstitution, folding, stability and function of a representative of the ubiquitous major facilitator transporter superfamily, lactose permease. Increasing the outward chain lateral pressure in the bilayer, through addition of lamellar phosphatidylethanolamine lipids, lowers lactose permease folding and reconstitution yields but stabilises the folded state. The presence of phosphatidylethanolamine is however required for correct folding and function. An increase in headgroup negative charge through the addition of phosphatidylglycerol lipids favours protein reconstitution but is detrimental to topology and function. Overall thein vitro folding, reconstitution, topology, stability and function of lactose permease are found to have different dependences on bilayer composition. A regime of lipid composition is found where all properties are favoured, even if suboptimal. This lays ground rules for rational control of membrane proteins in nanotechnology and synthetic biology by manipulating global bilayer properties to tune membrane protein behaviour.